Applications of AI-driven tools in translating and drafting commercial correspondence - Gajšt, Nataša (ELOPE (Ljubljana), 2025)
The recent emergence and the widespread use of AI-driven tools have significantly affected various aspects of human communication, including business-related professional communication. This pilot study explores how AI-driven tools can be used in drafting commercial correspondence by considering its genre conventions. To this end, we carried out a small-scale study to assess AI-driven tools for translating and drafting commercial correspondence. We used ChatGPT, Claude 3.5 Sonnet and Gemini 2.0 Flash to translate 15 letters from Slovenian into English and to draft 10 letters in English based on the prompts in Slovenian. Our key findings show that although the translations are similar, slight differences occur mainly at the level of formality and the scope of formulaic expressions. Concerning the drafts, the AI-driven tools produced adequate letters which might sometimes need light human editing.
Keywords: AI-driven tools; angleščina; Business English; commercial correspondence; drafting; English; orodja UI; pisanje; poslovna angleščina; poslovna korespondenca; prevajanje; Slovenian; slovenščina; translation